Influence of Social and Professional Characteristics on the Work Efficiency of Secondary Medical Staff (Statistical Indicators) - Turakulov Vali Norkulovich (Genius Journals, 2022)
The topic of the article is to provide the primary medical and sanitary care institutions of our country with employees who meet modern requirements in the rapidly changing and developing field of medicine, and for this, the work is being carried out to regularly update and reform the curriculum, teaching strategies and programs adopted in secondary medical education. The data obtained on this topic show that the improvement of professional performance depends on such issues as clinical strategies, improving the work environment, and developing the relationship between the employee and the patient.
Keywords: secondary medical worker; medical education; distance education; patronage nurse